(untitled) (Scientific journal of the Fergana State University, 2025)
This article describes the construction of a one-season water use plan for irrigation of crops of the farm “Ilkhom Ohun” under the conditions of irrigated meadow-sazov soils of Kushtepha district of Fergana region, specializing in the cultivation of grain and cotton.